Modeling of the process of heating of chip-powder dispersions of ferrous metals in the pass-through muffle furnace of hot briquetting. Message 3 - O. M. Dyakonov; A. A. Litvinko; V. Ju. Sereda (Литьë и металлургия, 2023)
It has been established that the optimal productivity of a 3,5 m high furnace in terms of the highest energy efficiency of its operation is 500 kg of chips per hour. It follows from the calculations and their analysis that it is practically possible to increase the productivity of the furnace by varying not only the operating parameters (power of the gas burner and inductor), but also the design parameters (furnace height, muffle flow area, number of burners and their effective location relative to the muffle).